(4 1/6)^12:(11 1/9)^6=
Răspunsuri la întrebare
Răspuns de
7
(4 1/6)^12:(11 1/9)^6=
4 1/6 = (4×6+1)/6 = 25/6
11 1/9 = (11×9+1)/9 = 100/9
= (25/6)^12 : (100/9)^6 =
= (25/6)^12 : (10/3)^12 =
= (25/6 : 10/3)^12 =
= (25/6 × 3/10)^12 =
= (5/6 × 3/2)^12 =
= (15/12)^12 =
= (5/4)^12
4 1/6 = (4×6+1)/6 = 25/6
11 1/9 = (11×9+1)/9 = 100/9
= (25/6)^12 : (100/9)^6 =
= (25/6)^12 : (10/3)^12 =
= (25/6 : 10/3)^12 =
= (25/6 × 3/10)^12 =
= (5/6 × 3/2)^12 =
= (15/12)^12 =
= (5/4)^12
Alte întrebări interesante
Chimie,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă